The role of renal biopsy in small renal masses - Burruni, Rodolfo; Lhermitte, Benoit; Cerantola, Yannick; Tawadros, Thomas; Meuwly, Jean-Yves; Berthold, Dominik; Jichlinski, Patrice; Valerio, Massimo (Canadian Urological Association Journal, 2016)
Renal biopsy is being increasingly proposed as a diagnostic tool to characterize small renal masses (SRM). Indeed, the wide adoption of imaging in the diagnostic workup of many diseases had led to a substantial increased incidence of SRM (diameter ≤4 cm). While modern ultrasound, computed tomography (CT) and magnetic resonance imaging (MRI) techniques have high sensitivity for detecting SRM, none is able to accurately and reliably characterize them in terms of histological features. This is currently of key importance in guiding clinical decision-making in some situations, and in these cases renal biopsy should be considered. In this review, we aim to summarize the technique, diagnostic performance, and predicting factors of nondiagnostic biopsy, as well as the future perspectives.